FEN1 mediates miR‐200a methylation and promotes breast cancer cell growth via MET and EGFR signaling. Issue 10 (2nd July 2019) - Zeng, Xue; Qu, Xiujuan; Zhao, Chenyang; Xu, Lu; Hou, Kezuo; Liu, Yunpeng; Zhang, Na; Feng, Jing; Shi, Sha; Zhang, Lingyun; Xiao, Jiawen; Guo, Zhigang; et al.
ABSTRACT: Flap endonuclease 1 (FEN1) is recognized as a pivotal factor in DNA replication, long‐patch excision repair, and telomere maintenance. Excessive FEN1 expression has been reported to be closely associated with cancer progression, but the specific mechanism has not yet been explored. In the present study, we demonstrated that FEN1 promoted breast cancer cell proliferation via an epigenetic mechanism of FEN1‐mediated up‐regulation of DNA methyltransferase (DNMT)1 and DNMT3a. FEN1 was proved to interact with DNMT3a through proliferating cell nuclear antigen (PCNA) to suppress microRNA (miR)‐200a‐5p expression mediated by methylation. Furthermore, miR‐200a‐5p was identified to repress breast cancer cell proliferation by inhibiting the expression of its target genes, hepatocyte growth factor (MET), and epidermal growth factor receptor (EGFR). Overall, our data surprisingly demonstrate that FEN1 promotes breast cancer cell growth via the formation of FENl/PCNA/DNMT3a complex to inhibit miR‐200a expression by DNMT‐mediated methylation and to recover the target genes expression of miR‐200a, MET, and EGFR. The novel epigenetic mechanism of FEN1 on proliferation promotion provides a significant clue that FEN1 might serve as a predictive biomarker and therapeutic target for breast cancer.—Zeng, X., Qu, X., Zhao, C., Xu, L., Hou, K., Liu, Y., Zhang, N., Feng, J., Shi, S., Zhang, L., Xiao, J., Guo, Z., Teng, Y., Che, X. FEN1 mediates miR‐200a methylation and promotes breast cancer cell growth via MET and EGFR signaling. FASEB J. 33, 10717–10730 (2019). www.fasebj.org